2003
DOI: 10.1056/nejme038109
|View full text |Cite
|
Sign up to set email alerts
|

The Prevention of Prostate Cancer — The Dilemma Continues

Abstract: Prostate cancer is the most common non-skin cancer in the United States, the second leading cause of death from cancer among U.S. men, and the seventh leading cause of death in the United States. The number of new cases of prostate cancer, now estimated at more than 220,000 per year, is expected to increase to more than 380,000 by 2025 because of the aging male population. The incidence of prostate cancer and the rate of death due to the disease increase exponentially with age. The other major risk factors for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
0
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(61 citation statements)
references
References 16 publications
2
54
0
5
Order By: Relevance
“…Concurrently, finasteride apparently had increased the risk of high-grade disease. Although high-grade tumors were a relatively small proportion of all detected tumors in the finasteride group, the potentially increased risk of aggressive disease and an unfavorable editorial accompanying the initial publication led to a general lack of acceptance of finasteride for cancer prevention (5). In the United States, early detection and treatment remain the primary focus for controlling this disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concurrently, finasteride apparently had increased the risk of high-grade disease. Although high-grade tumors were a relatively small proportion of all detected tumors in the finasteride group, the potentially increased risk of aggressive disease and an unfavorable editorial accompanying the initial publication led to a general lack of acceptance of finasteride for cancer prevention (5). In the United States, early detection and treatment remain the primary focus for controlling this disease.…”
Section: Introductionmentioning
confidence: 99%
“…We now know that finasteride enhances the detection of prostate cancer through the following effects on the performance characteristics of for-cause biopsies (see "Materials and Methods" section for definition): (a) improved sensitivity of prostate-specific antigen (PSA) for overall and high-grade cancer detection, (b) improved sensitivity of digital rectal examination (DRE) for cancer detection, and (c) more accurate grading of high-grade prostate cancer (5,6). Although these three detection biases would be expected to lead to cancer overdetection in study subjects receiving finasteride, there was a counteracting bias for greater cancer detection in the placebo group because these men more commonly underwent biopsy.…”
Section: Introductionmentioning
confidence: 99%
“…The results, published in 2003, showed that finasteride reduced the period prevalence of prostate cancer by 25% (5). However, the study results were criticized because of an observed increase in the risk of high-grade cancers (6). Subsequent studies have shown that this increase was likely an artifact of the detection process (7); a later report showed equivalent overall survival in the two study arms (8).…”
mentioning
confidence: 90%
“…The mortality/incidence ratios are given in Tables 4 and 5. It Increased mortality from prostate cancer represents the most significant change over this time period, and may be reflective of an ageing population, inadequate treatment, late clinical stage at diagnosis, or a combination of the three (7,8). This cancer ranks highest among the causes of cancer mortality in Antigua and Barbuda, and in the region (9,10).…”
Section: 8)mentioning
confidence: 99%